Conflitti, paci e vendette nell'Italia comunale - Andrea Zorzi (Reti Medievali E-Book, 2009)
This book is a collection of seven essays with an introduction by the editor. The contributions propose first-hand studies of some of the less researched aspects of the history of the Italian communes: the practices of conflict, vendetta and pacification. The variety of different ways of resolving conflicts brought to light by the studies for the various civic and rural contexts (Mantua, Parma, Pisa, Lucca, Florence and the Valdinievole), between the beginning of the thirteenth and the mid fourteenth century, indicate how normal such social relations were, the widespread nature of the feud and the legitimisation and centrality of the culture of the vendetta within the political arena of the commune. The book hence offers a precious contribution for a review of the prevalent narration of the vendetta in late mediaeval Italian society.